2005
DOI: 10.1124/jpet.105.092957
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase Mimetic Preserves the Glomerular Capillary Permeability Barrier to Protein

Abstract: Overproduction of superoxide (O 2 . ) occurs in glomerular disease and may overwhelm the capacity of superoxide dismutase (SOD), thereby intensifying oxidant injury by O 2 . and related radical species that disrupt the glomerular capillary permeability barrier to protein. We examined the efficacy of the SOD mimetic tempol in preserving glomerular permeability to protein using 1) a rat model of glomerular immune injury induced by an antiglomerular basement membrane antibody (anti-GBM), and 2) isolated rat glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…4). It has been demonstrated that oxidative stress plays a significant role in an increased glomerular filtration barrier permeability (15,33,34) and development of different kidney diseases, including adriamycin-induced injury (4), podocyte damage, and diabetic nephropathy progression (13,42). Our findings indicate that glomerular hemorrhage in WRN is independent of oxidative stress.…”
Section: Discussionsupporting
confidence: 56%
“…4). It has been demonstrated that oxidative stress plays a significant role in an increased glomerular filtration barrier permeability (15,33,34) and development of different kidney diseases, including adriamycin-induced injury (4), podocyte damage, and diabetic nephropathy progression (13,42). Our findings indicate that glomerular hemorrhage in WRN is independent of oxidative stress.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, Kida et al and Sato et al determined that a positive linear relationship exists between tubular dilatation and tubular epithelial apoptosis in UUO mice (18). Increased ROS, lipid peroxidation, and compromised antioxidants were previously found in a number of studies using obstructed rodent kidneys (6,24,35,48), and ROS have been suggested to impair the integrity of the glomerular basement membrane, reduce podocyte proteoglycan de novo synthesis, and stimulate factors promoting ECM deposition, including TGF-␤ 1 (9), as similarly observed in the present study. Overall, these results corroborate our results in the RTEC model system.…”
Section: Discussionsupporting
confidence: 74%
“…As such, free radical scavengers such as Tempol have been used extensively to ameliorate many of the biochemical abnormalities induced by hyperglycemia, including reduction of oxidant stress, in both in vitro cell culture and in vivo animal studies. 19,41 The contribution of ROS in our experimental system was studied by incubating HAECs with high glucose in the presence of 1 mM Tempol. Our results show that the glucose-induced impairment of flowinduced elongation and alignment occurs even in the presence of Tempol.…”
Section: Discussionmentioning
confidence: 99%
“…We first investigated the effect of ROS on the endothelial alignment response to flow using the common superoxide dismutase mimetic and free radical scavenger Tempol. 19,41 In representative images of shear-exposed cells (shown in Figs. 4a-4d), cells grown in 30.5 mM glucose + 1 mM Tempol 41 (Fig.…”
Section: High Glucose Impairs Flow-induced Elongation and Alignment Omentioning
confidence: 99%